Brain drain, remittances, and fertility - Luca Marchiori; Patrice Pieretti; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2008)
This paper analyzes the effects of skilled migration and remittances on fertility decisions at origin. We develop an overlapping generations model which accounts for endogenous fertility and education. Parents choose the number of children they want to raise and decide upon how many children obtain higher education. Only high skilled individuals migrate with a certain probability and remit to their parents. We find that an increase in the probability to emigrate leads both high and low skilled parents to send more children to obtain higher education. However the effect on the number of children is ambiguous. In a further analysis, we calibrate the model to match different characteristics of a developing economy. When the destination country relaxes the immigration restrictions, more high skilled individuals leave the origin country. The result is that, at origin, increased high skilled emigration reduces fertility and fosters human capital accumulation.
urn:nbn:de:hbz:361-14173
Keywords: F22; F24; J13; J24; 330; Skilled emigration; Remittances; Fertility; Human capital; Brain Drain; Fruchtbarkeit; Familienplanung; Rücküberweisung (Migranten); Facharbeiter; Akademische Berufe; Overlapping Generations; Industriestaaten; Entwicklungsländer